What Are Parents For?: REPRODUCTIVE ETHICS AFTER THE NONIDENTITY PROBLEM - Prusak, Bernard G. (The Hastings Center report, 2010)
Bioethicists often use the “nonidentity problem”—the idea that a child born with a disability would actually be a different child if she were born without the disability—to defend parents' rights to have whatever children they want. After all, a child is not harmed by being brought into the world with a disability; without the disability, she would not be brought into the world at all. But what happens if we turn the moral question around and ask, not about the benefits and harms to the child, but just about parental obligations? Will that lead to a different view of reproductive decisions?